Students’ perception using inquiry based learning in science experiment - Rubani, Siti Nur Kamariah; Ariffin, Arihasnida; Subramaniam, Tamil Selvan; Hamzah, Norhasyimah (UTHM Publisher, 2017)
Inquiry based learning is an approach that involves questioning, exploration of idea and solving the problem through discussion and exploration of information from the internet or scientific materials. The aim of this study was to identify the perception of student using inquiry based learning in science experiment based on their interest and confident level. A total of 30 respondents were selected through purposive sampling method. The respondents consisted of students’ from 5th grade at primary school in Malaysia. The data were analysed using descriptive statistic. The finding showed that using inquiry based learning can increase students interest (mean score = 4.19) and confident level (mean score = 4.32) during the experiment. Based on these findings, using inquiry based learning should be considered as the preferred method of teaching in science experiment.